Return and Retreat in a Transnational World: Insights from Eritrean Case - Cole, Georgia; Belloni, Milena (Refuge, 2022)
When refugees’ access to economic, political, and social rights cannot be guaranteed in one locale, individuals make pragmatic choices about what relationships to sustain with authorities elsewhere, even with those that caused their flight in the first place. This process of return is rarely akin to conventional repatriation, understood as the full re-establishment of the rights and responsibilities associated with citizenship (Bradley, 2013). In this paper, the authors instead propose the concept of retreat to capture the process initiated by those who are seeking to escape protracted displacement through a partial return to their country of origin, and through which individuals hope that they can assemble multiple sources of rights across several locations. Drawing from recent ethnographic research in Eritrea, the authors analyze the stories of individuals, mostly refugees, who have decided to retreat despite the lack of political change. Neither exclusively citizens nor refugees in countries of origin or asylum, research participants’ “dually absent” socio-legal position is analyzed in this article. The authors show that this rests on stratified forms of citizenship and the relational nature of different rights and statuses and argue that this position should be recognized as an additional dynamic in the literature on flight, return, and transnational citizenship.